Variation in Ozone at Night in Barrow, Alaska, during Different seasons, and its Relationship to Methane at Different Pressures - Vimal Kumar Saraswat; Nikunj Jaitawat (International Journal of Atmosphere, 2026)
The study is focus on the investigation of the night-time seasonal variability of ozone (O₃) at Barrow, Alaska, and also it examines its association with methane (CH₄) concentrations at different pressure levels along with solar flux variations on the basis of eighteen years (2003–2020) of observational data, including ground-based ozone measurements, satellite-derived methane data at 100, 200, 300, 400, and 500 hPa, and solar flux (F10.7) values. For finding the outcomes, monthly mean night-time data were computed and grouped into four seasons-winter, spring, summer, and autumn. The results indicate a consistent linear increase in methane concentrations across all seasons, with minimum growth observed at 100 hPa and maximum trends generally around 400 hPa. Methane trends exhibited strong statistical significance (above 95%) throughout the study period, suggesting limited seasonal influence on its increasing pattern. In contrast, ozone and solar flux predominantly showed decreasing trends during most seasons. Ozone exhibited notable seasonal variability, with comparatively stronger positive correlation with solar flux during the autumn season. The correlation analysis revealed that the solar flux and methane are generally negatively associated, while the relationship between the solar flux and ozone varies with seasons, with the highest positive correlation observed in October. Overall findings highlight the distinct seasonal behavior in ozone and methane dynamics at high latitudes and emphasize the importance of long-term night-time observations or understanding atmospheric chemistry, greenhouse gas interactions, and their implications for climate variability in the Arctic region.
Keywords: Arctic atmosphere; Methane trends; Ozone variability; Seasonal variation; Solar flux